2019
DOI: 10.26444/aaem/94294
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of occupational burnout among employees of the Emergency Medical Services in Poland

Abstract: Introduction. Occupational burnout is a multifaceted phenomenon and a problem often encountered among medical personnel. An example of such a group are workers of the Emergency Medical Services (EMS). The aim of the present study was to make an attempt to assess the level of job burnout among professionally active employees of the EMS and to compare the different occupational groups (paramedics, nurses of the system, doctors of the system) according to four analyzed factors. Materials and methods. A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
3
22
0
6
Order By: Relevance
“…And in fact, there was a significant difference in the occupational stress of technicians working in emergency medical services and other services (earthy emergency medical services, emergency medical departments, etc.) and they had clearly experienced less stress [23]. Similar results were obtained in other medical groups, and Yuwanich et al showed that nurses in the emergency medical department were more exposed to occupational stress compared to nurses in other sections due to their higher workload [15].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…And in fact, there was a significant difference in the occupational stress of technicians working in emergency medical services and other services (earthy emergency medical services, emergency medical departments, etc.) and they had clearly experienced less stress [23]. Similar results were obtained in other medical groups, and Yuwanich et al showed that nurses in the emergency medical department were more exposed to occupational stress compared to nurses in other sections due to their higher workload [15].…”
Section: Resultssupporting
confidence: 61%
“…Leszczynski et al showed that physicians and nurses in the emergency medical services department suffered more burnout compared to emergency medical personnel. They stated that emergency medical service personnel experienced the least amount of burnout compared to their colleagues [23]. Yuwanich et al in Thailand announced that nurses of emergency medical services department are more at risk of occupational stress compared to nurses in other departments and less work experience is related to the stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…Leszczyński et al reported that the EMS employees experience varying degrees of occupational stress depending on the place of work because the technicians working in air EMS services had experienced less stress than other services (ground EMS services, emergency departments, etc.) [37]. Other medical groups revealed similar results.…”
Section: Discussionsupporting
confidence: 60%
“…Leszczynski et al emphasized that physicians and nurses in the emergency medical services department suffered more burnout than emergency medical personnel did. They stated that emergency medical service personnel experienced the least amount of burnout compared to their colleagues [37]. Besides, the problems discussed above, emergency medical personnel employed by the Iranian Government's health-care system are involved in addressing other challenges, such as staff shortages, inadequate equipment, inadequate training of the necessary standards, interaction with people, skills training issues, anxiety and various forms of emotional distress [9,38].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Makara-Studzinska et al every second physician showed a high level of BS [55], while Czekajska-Chehab et al reported 37% of the examined population [36]. On the other hand, Leszczynski et al reported 16% [54], whereas Misiolek et al reported 18% [52]. Nevertheless, a vast majority of the articles focused on the severity of individual symptoms.…”
Section: Bs In Physicians In Poland and Worldwidementioning
confidence: 99%